Bayesian Optimization with Resource Constraints and Production - Dolatnia, Nima; Fern, Alan; Fern, Xiaoli (Proceedings of the International Conference on Automated Planning and Scheduling, 2016)
In this paper, we aim to take a step toward a tighter integration of automated planning and Bayesian Optimization (BO). BO is an approach for optimizing costly-to-evaluate functions by selecting a limited number of experiments that each evaluate the function at a specified input. Typical BO formulations assume that experiments are selected one at a time, or in fixed batches, and that experiments can be executed immediately upon request. This setup fails to capture many real-world domains where the execution of an experiment requires setup and preparation time. In this paper, we define a novel BO problem formulation that models the resources and activities needed to prepare and run experiments. We then present a planning approach, based on finite-horizon tree search, for scheduling the potentially concurrent experimental activities with the aim of best optimizing the function within a limited time horizon. A key element of the approach is a novel state evaluation function for evaluating leaves of the search tree, for which we prove approximate guarantees. We evaluate the approach on a number of diverse benchmark problems and show that it produces high-quality results compared to a number of natural baselines.